Are You SURE You want to waste policy chances? Waste generation, landfill diversion and environmental policy effectiveness in the EU15 - Valentina Iafolla; Massimiliano Mazzanti; Francesco Nicolli (Fondazione Eni Enrico Mattei (FEEM), 2010)
We empirically test delinking of waste dynamics with regard to economic growth and the effectiveness of environmental and specific waste-related policies, by exploiting a newly constructed, integrated waste-economic-policy dataset based on official data for the EU15 for 1995-2007. We find that absolute delinking for waste generation is far from being achieved in the EU despite fairly stringent and longstanding policy commitment that goes back to the mid 1990s, but which however is biased towards waste management and waste disposal rather than waste prevention. Policy as well as country structural factors seem to impact instead on landfill diversion. Nevertheless, country heterogeneity matters: SURE based analyses show that EU average figures often hide high variance. Their results provide food for thought for a future most comprehensive EU waste policy strategy, which is now aimed mainly at landfill diversion, within a framework strongly oriented to allowing countries to decide about the implementation of EU directives.
Keywords: C23; Q38; Q56; 330; Waste Generation; Landfill Diversion; SUR; EU Waste Policy; Environmental Policy; Delinking